FORMATION OF PROFESSIONAL JOURNALISTS A FUTURE UNDER UNIVERSITY STUDY - Хоменко-Семенова, Л. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article describes the professional quality of journalists, describes the requirements for professional journalists innovative society, identified the main characteristics of the journalist from the works of contemporary Ukrainian scholars. The model of professional portrait professional journalism, which describes the professional, moral, psychological, civil qualities. Analyzes innovative teaching technologies that contribute to the formation of professional skills of future journalists in the course of vocational training, such as: Internet technology, multimedia technology, case-study, brainstorming, interactive games